Maize (Zea mays, L.) response on Fertilization of Russian MOP in Inceptisols and Ultisols - DEDI NURSYAMSI; . HUSNAIN; ANTONIUS KASNO; DIAH SETYORINI (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2005)
Indonesia’s agricultural lands commonly require fertilization of K to attain optimum plant yield. So far, most farmers use K fertilizer from KCl, apart to the fact that its effectiveness varies with soils and plants. It is expected that Russian MOP fertilizer is more effective and economically morebeneficial than KCl fertilizer. Field experiment aimed to test the effectiveness of Russian MOP for maize and was conducted in Inceptisols (of Cibatok-Bogor) and Ultisols (of Jagang-North Lampung) in dry season of 2004. The experiment applied Randomized Completely Block Design with 3 replicates, and maize of Lamuru variety was as plant indicator. The treatment consisted of 5 levels of Russian MOP fertilizer: 0, 25, 50, 100,and 200 kg ha-1 and one treatment of KCl fertilizer of 100 kg ha-1 as a reference. The result showed that the use of Russian MOP increased soil HCl-K and NH4OAc-K as well as dry matter and grain yield. RAE at Russian MOP level of > 100 kg ha-1 was 138 and 115 in Inceptisols of Cibatok and 314 in Ultisols of Jagang. The maximum profits using Russian MOP fertilizer in Inceptisols and Ultisols were Rp 4.4 and Rp 1.9 million ha-1 season-1, respectively, and were greater than those of using KCl fertilizer in both studied soils. IBCR values of the Russian MOP fertilizer were 2.44-10.37 (Inceptisols) and 0.69-3.41 (Ultisols) and were greater than those of KCl fertilizer. The requirements of Russian MOP fertilizer to achieve maximum profit were 119 and 105 kg ha-1 or equal to 71 and 63 kg K2O ha-1 for Inceptisols of Cibatok and Ultisols of Jagang, respectively. Considering its effectiveness and benefit, Russian MOP fertilizer can be used as alternative of K fertilization.